Yamato-74063: Chondritic meteorite classified between E and H chondrite groups - Yanai, Keizo; Kojima, Hideyasu (National Institute of Polar Research, 1991)
P(論文) Yamato-74063 (Y-74063) was found in Antarctica by the Japanese Antarctic Research Expedition in November 1974. Y-74063 is an almost complete, smoothly rounded stone weighing 35.4g covered with brownish-black fusion crust. The thin section shows that this meteorite has generally poorly traced chondritic texture and "chondrules" merge into the recrystallized matrix. Compositions of olivine and low-Ca pyroxene are homogeneous and average Fa_<10.9> and Fs_<10.7> respectively. These compositions strongly suggest that Y-74063 is not similar to all the previously known chondrites. Bulk analysis shows that the total iron content of Y-74063 is the lowest of the ordinary chondrite groups, and the abundance of troilite is much higher than those of all ordinary chondrites. Texture, bulk and mineral compositions of Y-74063 indicate that this meteorite is identified as chondrite and classified into a new type of chondrite group which is between E and H chondrite groups. Y-74063 is similar to Acapulco, ALH-77081 and ALH-78230 in mineral composition which occupies the intermediate site between the E and H chondrites. But the latter 3 chondrites have no evidence of chondrules in spite of "chondritic" texture, mineral assemblage and compositions. Bulk composition indicates that Y-74063 differs from Acapulco-type meteorites and all previously known chondrite groups. The presence of Y-74063 suggests that there is a great possibility of the existence of more unknown meteorite types in Antarctica, and non-Antarctic regions. departmental bulletin paper